PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE 3 UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA TEMA PANAS DAN PERPINDAHANNYA DI KELAS VSD BUNGA TANJONG - Nurnisa Kamila; Samsul Bahri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to: (1) To determine the development of articulate storyline 3 learning media in order to increase students' interest in learning about hot themes and their transfer in class V of Bunga Tanjong Private Elementary School. (2) To determine the feasibility of Articulate Storyline 3 learning media in increasing students' interest in learning about hot themes and their transfer in class V of Bunga Tanjong Private Elementary School. This research is a type of research and development referring to the ADDIE model which stands for Analyze, Design, Development, Implementation, Evaluation. The instrument used to collect data was a questionnaire. Data analysis techniques are descriptive qualitative and quantitative. From the validation results of class V teacher responses, it can be seen that the quality of the articulate storyline media on hot and moving themes got a percentage of 85%. The results of the validation of the assessment by media experts got a score of 96% from 13 statements. The results of the validation of the assessment by material experts got a score of 95% from 10 statements. The results of the validation of the student response assessment obtained 95% of the 8 statements. The articulate storyline that has been developed can be applied as a first step in the teaching and learning process in schools, so that the articulate storyline on hot themes and its transfer shows the criteria to be very valid or very feasible.